Transformational Leadership, Emotional Itelligence and Psyhcological Capital and its Impact on Work Engagement and Job Performance PT.Telkom Indonesia - Ricka Yulianthi; Justine Tanuwijaya (Jurnal Manajemen Bisnis, 2023)
The findings of this research demonstrate that there is a favourable correlation between transformational leadership, emotional intelligence, and psychological capital, and the level of job satisfaction among TELKOM employees. Furthermore, it is worth noting that job happiness has been found to have a favourable impact on both work engagement and employee performance. The present study employed the Partial Least Squares Structural Equation Modelling (PLS-SEM) methodology, and data was gathered using a questionnaire administered to a sample of 212 participants. The findings of this study suggest several recommendations for enhancing work engagement and employee performance among TELKOM employees. These recommendations include enhancing transformational leadership, emotional intelligence, psychological capital, and job happiness. By focusing on these areas, organisations can potentially improve the overall engagement and performance levels of their employees.